Beyond Maps. A Workshop on Users’ Sense of Place and Visual Representation at Milano-Bicocca University - Agrestini, Alessandra; Colleoni, Matteo; Mangiatordi, Andrea; Malatesta, Stefano; Nuvolati, Giampaolo; Squarcina, Enrico; Zuccoli, Franca (img journal, 2022)
In a trans-scalar perspective, the Bicocca district extends from the local NIL (Nucleo di Identità Locale) to part of Municipality 9, Sesto San Giovanni and Cinisello Balsamo. Recently, the University of Milan-Bicocca, as regards to the so-called ‘terza missione’, has remarked its role as a key-pole for the surrounding area by proposing research, educational (and orientation) activities, as well as institutional initiatives based in this post-industrial area of Milan. Within this scenario, our group was in charge of design-ing a project leading to an artistic image representing the district users’ sense of place. By combining geography of perception, urban sociology, participatory design and the flânerie approaches, we planned a working process starting from the ‘subjective production of images’ by the district’s users and inhabitants. The project was structured in two phases: (1) December 2020 – January 2021: we organised two workshops by inviting groups of students, teachers and shop owners and working on their mental maps to construct a final image resulting from the two teams’ negotiation processes. The reading of the maps was initially inspired by the categories identified by Kevin Lynch (1962) and then moved on to a process of co-construction of a collective image; (2) March 2021: we shared the visual body with a professional illustrator (Carlo Stanga) entrusted with the mandate to translate the images into an artistic product. The essay discusses the visual representation of users’ sense of place and the potential legacy upon communication strategies, way-findings tools and education projects.